2012
DOI: 10.1116/1.4766880
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of nonreactive fluoroalkyl-containing surfactants for reducing release energy of ultraviolet-cured acrylate resins

Abstract: The authors investigated the types of additive nonreactive fluorinated surfactants that effectively decrease the release energy of a certain ultraviolet-cured base resin for radical photopolymerization. The release energies of resins containing various surfactants were compared in two atmospheres, namely air and 1,1,1,3,3-pentafluoropropane (PFP, HFC-245fa). Tridecafluoro-1,1,2,2-tetrahydrooctan-1-ol functioned as the most effective surfactant under an air atmosphere, for detachment of a silica surface modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The remaining liquified condensable gas is assumed to remain as a thin PFP-rich layer between the mold and resist, or dissolves in the resist [ 34 , 36 ]. Since PFP contains fluorine and exhibits low surface energy, such a layer is suggested to effectively decrease the release energy (i.e., demolding force; see Figure 2 ) of the cured resist compared to that in air [ 34 , 36 , 37 , 38 ]. On the other hand, the use of condensable gas may be disadvantageous due to pattern height shrinking via absorption by the resist [ 39 ].…”
Section: Characteristics and Issues In Thermal And Uv Nanoimprint Lithographymentioning
confidence: 99%
“…The remaining liquified condensable gas is assumed to remain as a thin PFP-rich layer between the mold and resist, or dissolves in the resist [ 34 , 36 ]. Since PFP contains fluorine and exhibits low surface energy, such a layer is suggested to effectively decrease the release energy (i.e., demolding force; see Figure 2 ) of the cured resist compared to that in air [ 34 , 36 , 37 , 38 ]. On the other hand, the use of condensable gas may be disadvantageous due to pattern height shrinking via absorption by the resist [ 39 ].…”
Section: Characteristics and Issues In Thermal And Uv Nanoimprint Lithographymentioning
confidence: 99%
“…We have reported that laser-drilled screen printing with unmodified PI masks are applicable to (fluorescent) UVcurable liquids of NL-SK1(F) and NL-SU1(F) showing a viscosity of 12.8 and 11.0 Pa s, respectively, and a fluorescent glycerin showing a viscosity of 1.4 Pa s. 24,25,29) Here, we investigated whether the unmodified PI masks were available for a GDM-based UV-curable liquid with a low-viscosity of 0.10 Pa s to lower the range of viscosity applicable to laserdrilled screen printing. According to our previous study, 25) 100 through holes with a mean hole diameter of 9.3 μm on a substrate-contact-side surface were prepared with a pitch of 100 μm by laser drilling onto an area of 1.0 × 1.0 mm 2 of a PI film surface.…”
Section: Screen Printing Of a Low-viscosity Gdm-based Liquid With Unm...mentioning
confidence: 99%
“…A commercially available silica mold (NTT-AT NIM-PH-350, 10 × 10 mm 2 ) with 350 nm-10 µm line-and-space, hole, and dot patterns was modified with tridecafluoro-1,1,2,2-tetrahydrooctyltrimethoxysilane (FAS13) as an antisticking agent by chemical vapor surface modification. 30) The UV nanoimprint process comprised five steps: (i) moving the fluorinated mold close to a thin resin film or resin droplets on a silicon substrate at a speed of 20 µm s −1 , (ii) increasing the applied pressure to 1.0 MPa, (iii) holding the position for load adjustment in 30 s, (iv) curing molded resin by exposure to UV light emitting from light-emitting diode arrays at a wavelength of 365 nm and a light intensity of 50 mW cm −2 for 20 s, and (v) demolding at a speed of 4,000 µm s −1 . Imprint resist patterns were observed by fluorescence microscopy under an optical microscope (Olympus BX51) equipped with a fluorescence cube (Olympus U-MWIG3, excitation wavelengths, 530-550 nm; detection wavelengths, >575 nm), an objective lens (Olympus UPlanS Apo 10×=0.40), and a charge-coupled device (CCD) camera (Hamamatsu Photonics ORCA-R2).…”
Section: Uv Nanoimprinting Of Spin-coated Resin Films and Discharged ...mentioning
confidence: 99%